Levels of Digital Maturity of Regional Governance - E. V. Popov (Ekonomika Nauki)
Decree of the President of Russia No. 1014 has identified ‘digital maturity of state and municipal management’ as one of the key indicators of the effectiveness of senior officials in the subjects of the Russian Federation. A unified assessment of digital maturity is particularly critical at the level of regional authorities. The purpose of this study is to develop a framework for assessing the levels of digital maturity within regional governance. The study employed the method of systemic logical analysis and the structural-functional approach to examine regional management teams and the functions of regional managers. The information base for the study comprises articles indexed in the global ScienceDirect database and the national eLIBRARY database, using search keywords such as ‘levels of digital maturity of regional authorities.’ As a result of the research, a typology of six levels of digital maturity in regional governance has been proposed: absence, existence, application, utilization of digital technologies, replacement of managerial functions with digital technologies, and autonomous regional governance without human involvement. The study demonstrates the feasibility of conducting an objective analysis of digital maturity by evaluating the proportion of management decisions based on digital technologies. Furthermore, the article examines the evolving role of regional leaders in the decision-making process through the integration of digital technologies, transitioning from decision-making without considering digitalization to becoming architects of digital processes and technologies. The study also highlights that the determination of digital maturity levels in regional government bodies can be achieved through the method of transactional tomography. The findings contribute to the theoretical foundation for assessing the digitalization processes within territorial governance structures.